Hubungan antara Asupan Makanan dan Status Kekurangan Energi Kronis pada Calon Pengantin Pasangan Usia Subur - Agustri, Putri Ranatul; Rosyidah, Haqqelni Nur; Pratiwi, Siska (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
The prevalence of Chronic Energy Deficiency (CED) in the Riau Islands is a concerning public health issue, with 18.7% of non-pregnant women reported to be affected. In Batam City specifically, 95 cases of undernutrition were recorded in 2024. This study aimed to analyze the relationship between food intake and the nutritional status of women of reproductive age experiencing CED. A descriptive correlational research design with a cross-sectional approach was employed. The study used total sampling, involving 31 women from the Batu Aji KUA in Batam. Data on food intake were collected and compared to recommended dietary standards. The findings indicated that a majority of women had food intake levels below the recommended daily allowance. Despite this, not all of the participants were found to be suffering from CED. Statistical analysis using the Chi-square test revealed a significant association between food intake and nutritional status (p = 0.025, where α = 0.05), suggesting that food intake plays an influential role in determining nutritional outcomes. Furthermore, women whose food intake was lower than the recommended levels were found to have a 0.611 times greater risk of experiencing chronic energy deficiency. These findings emphasize the crucial role of adequate energy and nutrient intake, especially among women of reproductive age, in preventing CED and improving overall health. Improving food consumption patterns in this demographic is essential not only for individual well-being but also as a preventive measure to reduce the risk of stunting in future generations. The study underscores the need for targeted educational interventions to increase awareness about proper nutrition and energy intake among women, particularly those in reproductive age, as a strategy to address undernutrition and its broader public health consequences.